Effect of adding a compassion-focused intervention on emotion, eating and weight outcomes in a commercial weight management programme. (September 2021) - Duarte, Cristiana; Gilbert, Paul; Stalker, Carol; Catarino, Francisca; Basran, Jaskaran; Scott, Sarah; Horgan, Graham; Stubbs, R James
This study examined whether adding a compassion-focused light touch digital intervention into a commercial multicomponent weight management programme improved eating behaviour, self-evaluation and weight-related outcomes. The compassion intervention significantly reduced binge eating symptomatology and dropout, and improved psychological adjustment and self-evaluation, but did not affect weight outcomes. Compassion, self-reassurance and reductions in shame and self-criticism mediated the effect of the intervention on reductions of binge eating symptomatology. Negative self-evaluation, binge eating symptomatology, susceptibility to hunger and eating guilt were significant predictors of dropout. Findings suggest that compassion-based digital tools may help participants better manage binge eating symptomatology and self-evaluation in weight management interventions.